2014
DOI: 10.3402/rlt.v22.21635
|View full text |Cite
|
Sign up to set email alerts
|

Using social media to engage and develop the online learner in self-determined learning

Abstract: Social media technology provides educators with an opportunity to engage learners in the online classroom, as well as to support development of learner skills and competencies. This case study explores the role of social media in promoting cognitive and meta-cognitive learner development while using a heutagogical teaching and learning approach. Research was conducted using questionnaires and interviews and incorporated the perspectives of both students and instructors on the use of social media in the online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 15 publications
4
104
0
8
Order By: Relevance
“…Moreover, studies acknowledge an increase of social media use in human activities (Blaschke 2014;Mnyanyi et al 2010). Regardless of the negative experience that users of social media may have experienced, a well-planned use brings positive benefits to the society (Chawinga 2017;Jovanovic & Chiong 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies acknowledge an increase of social media use in human activities (Blaschke 2014;Mnyanyi et al 2010). Regardless of the negative experience that users of social media may have experienced, a well-planned use brings positive benefits to the society (Chawinga 2017;Jovanovic & Chiong 2012).…”
Section: Resultsmentioning
confidence: 99%
“…One of the areas to be benefited is the learning process. Social media provide the opportunity for educators to engage learners in online classrooms (Blaschke 2014;Bora & Ahmed 2013). In this study, it was important to understand how higher learning students adopt social media in the learning process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blaschke [13] indicated that social media alone will not develop learners, rather it is a combination of course design and delivery with the technology that creates an environment for learning. Incorporating social media into an assignment can also positively reinforce student engagement [33].…”
Section: Perceptions Of Social Media Use In Curriculum Design and Leamentioning
confidence: 99%
“…There are several potential benefits to using social media in college settings that catalyze student participation in social media, institutional events, and course related activities (Blaschke, 2012(Blaschke, , 2014. For example, students may configure their social media accounts to stream campus news and announcements to be notified about campus and community events and developments (Achen, 2015;Junco, 2012).…”
Section: Potential Academic Benefits Of Student Engagement In Social mentioning
confidence: 99%